South African Renal Registry Annual Report 2019 - Davids, M Razeen; Jardine, Thabiet; Marais, Nicola; Sebastian, Sajith; Davids, Thaabit; Jacobs, Julian C (African Journal of Nephrology, 2021)
The eighth annual report of the South African Renal Registry summarises the 2019 data on kidney replacement therapy (KRT) for patients with kidney failure in South Africa. This round of data collection has been adversely affected by the COVID-19 pandemic, which has impacted on the completeness of the data. In December 2019, the number of patients who were being treated with chronic dialysis or transplantation stood at 9 937, a prevalence of 169 per million population (pmp). The prevalence in South Africans accessing the private healthcare sector was 788 pmp, whereas it was 57 pmp in the chronically under-resourced public sector, still below the rate reported for 1994.